TANGGAP TANAMAN JAGUNG TERHADAP PEMUPUKAN KALIUM DAN PEMBUATAN PARIT PADA LAHAN KERING - Edy Edy; Didik Indradewa2; Dja’far Shiddieq (Percetakan Umi Toaha Makassar, 2020)
Water management in rainfed dry land is very important to consider. Limited water on dry land can be pursued with rain harvesting technology among others, by making a furrow filled with organic matter in situ. In anticipation of drought stress during the growth period of maize given the optimum potassium fertilizer to make it more survive when low rainfall that the productivity results remain stable. This study aims to determine response of masize to potassium fertilization and treatment of furrow on improvement of maize yield on dry land. The research was conducted in the Village of Wareng, sub District of Wonosari, District of Gunungkidul Province of D.I. Yogyakarta, which take place from November 2010 - February 2011. The design used is the design of Splite plots, with the main plot is designed in a Latin Square. The main plot is the trench model consists of three standard Furrows: Without the furrow (Control, P0), Furrow (P1), Furrow+organic matter (P2). Potassium fertilization subplot is comprised of 3 levels: without potassium fertilization (control, K0), 37.5 kg KCl.ha-1 (K1) and 75 kg KCl.ha-1 (K2). To obtain 9 combined treatment was repeated 3 times. Corn varieties tested were Bima-2 Bantimurung. The results showed that the combination of furrow+ organic matter and 75 kg KCl.ha-1 can increase soil moisture between 3-17%, plant growth rate 35-85%, water-use efficiency 33% and yield of corn per hectare 30%.